Construction of Entrepreneurial Indentity Among Maritime Transportation Student In The Digital Maritime Business Ecosystem - Marleny Syam (Jurnal Penelitian Samudra, 2026)
The rapid digital transformation of the maritime industry has fundamentally reshaped the career orientation of maritime transportation students, shifting their aspirations from conventional employment in the shipping industry toward technology-driven entrepreneurship. This transition has created a new digital maritime business ecosystem that not only generates economic opportunities but also facilitates the social construction of entrepreneurial identity. This study aims to examine the process through which maritime transportation students construct their entrepreneurial identity within the digital maritime business ecosystem and to identify the internal and external factors influencing this process. A qualitative approach employing an interpretative phenomenological design was adopted. Data were collected through in-depth interviews with twelve maritime transportation students actively operating digital maritime businesses. Additional data were obtained from digital business documentation and observations of participants' social media activities. The collected data were analyzed using data reduction, thematic categorization, and contextual interpretation. The findings reveal that entrepreneurial identity develops through three interconnected stages: identity exploration, social legitimization, and entrepreneurial role internalization. This process is shaped by the interaction between personal motivation, entrepreneurial self-efficacy, supportive entrepreneurial communities, and the utilization of digital ecosystems, including social media and maritime digital business platforms. Furthermore, digital transformation within the logistics and shipping industries has significantly influenced students' career preferences by encouraging technology-based entrepreneurial activities. The study concludes that entrepreneurial identity in the context of digital maritime business represents a dynamic socio-digital construct emerging from the integration of entrepreneurial experience, digital presence, and ongoing industrial transformation. These findings contribute to the theoretical development of entrepreneurial identity research while offering practical implications for strengthening digital-based maritime entrepreneurship education in higher education institutions.